Neurocognitive endophenotypes of schizophrenia and bipolar disorder and possible associations with FKBP variant rs3800373 - Memic, Amra; Streit, Fabian; Hasandedic, Lejla; Witt, Stephanie; Strohmaier, Jana; Rietschel, Marcella; Oruc, Lilijana (Medicinski arhiv, 2018)
Introduction: Schizophrenia(SCZ) and Bipolar disorder (BD) are frequently occurring and impairing disorders that affect around 1% of the population. Important endophenotypes in the genetic research of SCZ and BD are cognitive functions. Core symptoms for SCZ and BD are impairments in working memory, declarative memory and attention, all of which fulfill the criteria for an endophenotype. The FK506 Binding Protein 5 (FKBP5) gene codes for a co-chaperone of the glucocorticoid receptor and has been reported to be associated with cognition. - Aim: The aims of our research were to determine the degree of cognitive impairment in patients suffering from SCZ and BD and to explore the association of the FKBP5 variant rs3800373 genotype with the cognitive endophenotypes. - Material and Methods: Patients and healthy controls were recruited over a period of two years from the Psychiatric Clinic, Clinical Center University of Sarajevo. Genotyping and neuropsychological assessments were performed for 263 subjects (129 SCZ, 53 BD, and 81 healthy controls [HC]). Neuropsychological assessments were performed for all patients with the Trail Making Test-A&B (TMT-A&B) and Digit-span forward&backwards tasks. The single nucleotide polymorphism (SNP) rs3800373 in the FKBP5 gene was genotyped using Infinium PsychArray Bead Chips. - Results and Conclusion: SCZ and BD patients performed lower than HC in the TMT-A&B and in the Digit-span backwards task, while no differences were observed between SCZ and BD patients. While SCZ patients performed lower than HC in the Digit-span forwards task, there were no differences between BD and HC or between BD and SCZ. Rs 3800373 was not associated with performance in the TMT-A&B or Digit-span forwards&backwards tasks. SCZ and BD share largely overlapping neurocognitive characteristics. Rs3800373 was not associated with performance in the neuropsychological tests. However, given the limited sample size, the results do not exclude an association with the rs3800373 variant in a larger sample. Furthermore, as the analysis was limited to one SNP, the results cannot be generalized to other genetic variants in FKBP5.
Gesehen am 30.03.2020